Effectiveness of dermoscopy in the demarcation of surgical margins in slow Mohs surgery. Issue 6 (7th September 2020) - Litaiem, Noureddine; Karray, Manel; Jones, Meriem; Rammeh, Soumaya; Zeglaoui, Faten
Abstract: There is a need for adjuvant imaging techniques that would allow reducing the number of slow Mohs stages. This study aimed to evaluate the use of dermoscopy in the demarcation of basal cell carcinoma (BCC) surgical margins for slow Mohs surgery. This was a retrospective study over 3 years (2016‐2019), including patients with BCC excised using slow Mohs surgery. On the basis of the treatment received, the patients were divided into 2 groups: group 1 (28 BCC) and group 2 (26 BCC). In group 2, BCC margins were demarcated using dermoscopy. A total of 54 patients were enrolled in the study. The number of positive lateral margins was significantly lower in the group where BCC margins were demarcated using dermoscopy (19% vs 53%, P = .012). In this group, the number of Mohs stages needed to achieve complete clearance was significantly lower. However, the mean interval between the first Mohs excision and Mohs clearance was not significantly different between the 2 groups (9 ± 4 vs 12 ± 7 days). In conclusion, preoperative dermoscopy is useful for reducing the number of positive lateral margins and the number of slow Mohs stages in treating BCC especially pigmented tumors.